2016
DOI: 10.1111/jth.13478
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of superficial and deep vein thrombosis associated with peripherally inserted central catheters in children

Abstract: Background Upper-extremity venous thrombosis is associated with the use of peripherally inserted central catheters (PICCs). Few pediatric studies have focused on this issue. Objectives To determine the incidence and risk factors for PICC-related superficial vein thrombosis (SVT) and deep vein thrombosis (DVT) in children. Patients/methods An observational follow-up cohort study was conducted at a single hospital between June 2012 and June 2015. All patients receiving a PICC were enrolled and followed up, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 65 publications
6
69
0
3
Order By: Relevance
“…For the entire study cohort, CVL indwelling time of >28 days was shown to be associated with a significantly higher incidence of aVTE compared to those with <28 days (29%, 95% CI: 17%‐23% versus 13%, 95% CI: 9%‐18.6%; P < .01). Several studies chose a 7‐day time point showing that indwelling time longer than 7 days increased the risk of aVTE . The same 7‐day time point was confirmed in an RCT evaluating continuous infusion of UFH for prevention of CVL‐related VTE in young infants with cardiac disease .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For the entire study cohort, CVL indwelling time of >28 days was shown to be associated with a significantly higher incidence of aVTE compared to those with <28 days (29%, 95% CI: 17%‐23% versus 13%, 95% CI: 9%‐18.6%; P < .01). Several studies chose a 7‐day time point showing that indwelling time longer than 7 days increased the risk of aVTE . The same 7‐day time point was confirmed in an RCT evaluating continuous infusion of UFH for prevention of CVL‐related VTE in young infants with cardiac disease .…”
Section: Resultsmentioning
confidence: 93%
“…For patients requiring short‐term CVLs (<30 days), surveillance imaging was mostly performed within 24 to 72 hours after CVL placement and then serially at a 3‐ to 7‐day interval as long as CVL was in place and then at the time of CVL removal until a week after CVL removal . The majority of aVTE were detected within 2 to 7 days of CVL placement .…”
Section: Resultsmentioning
confidence: 99%
“…In the more general pediatric population, the prevalence of lineassociated thrombosis is not well understood, but the authors of 1 study of 265 children who underwent peripherally inserted central catheter placement for various indications found that ∼8% had line-associated thromboses, the majority of which were asymptomatic. 10 The exhaustion of central venous access sites due to recurrent thrombosis is a potentially fatal complication for patients who rely on PN or intravenous medications. Indeed, the American Society of Transplantation lists the impending loss of central venous access as an indication for intestinal transplantation in infants and children receiving PN for IF.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis and intraluminal occlusions are the most common cause of PICC failure in pediatric patients (Menendez et al 2016;Morgenthaler and Rodriguez 2016). A recent development in PICC material involves the incorporation of antithrombogenic material (Endexo™) throughout the catheter-the inside, the outside, and the cut surface.…”
Section: Catheter Materials and Designmentioning
confidence: 99%